Reconstruction of Islamic Cultural History Learning in Madrasah Ibtidaiyah Through Project Based Learning: A Study of Historical Engagement and Internalization of Islamic Character Values - Sariyani (Jurnal Kependidikan Islam, 2026)
Learning Islamic Cultural History (SKI) in Madrasah Ibtidaiyah (MI) is still dominated by the transmissive learning approach that prioritizes the memorization of facts related to historical events, causing low student participation and comprehension. The objectives of this research are to explain how the implementation of the reconstruction of SKI learning through Project-Based Learning (PjBL) was designed, as well as to analyze its contributions in improving students' historical engagement and the internalization of Islamic character values. A qualitative case study method was applied at MI Mansyaul Ulum Grobogan. Semi-structured interviews, participatory observation, and documentation served as data collection methods, which were then analyzed using the Miles-Huberman-Saldana interactive thematic analysis model. It was found that the reconstruction of SKI learning through PjBL has greatly improved student participation, comprehension of historical facts, and the internalization of the exemplary characters of Khulafaur Rasyidin. The implementation of PjBL employed six integrated PjBL process stages, complemented by interactive lectures as a conceptual foundation before project development began. Infographics, short dramas, and booklets created by students demonstrated not only students' comprehension of historical events, but also their internalization of honesty, justice, generosity, and courage drawn from the stories of Khulafaur Rasyidin.